Liderança romantizada: um estudo na Universidade Federal de Santa Maria a partir da Romance of Leadership Scale (RLS) - Dagort, Felipe (2017)
Federal University of Santa Maria (UFSM) comprehends leadership as a cornerstone for its administration, according to Institutional Development Plans from 2011 to 2015 and 2016 to 2026, factor also observed by the emphasis on university’s manager training program, which is called Lidere. However, leadership is not a construct with a unanimous definition in neither theoretical nor practical terms. Thus, from the perspective of the Romance of Leadership from Meindl, Ehrlich e Dukerich (1985), which points to a tendency of having an idealized vision of the leader, this study aimed to investigate the degree of romance of leadership that public servants of the Federal University of Santa Maria present. In order to achieve this goal, methodology mixes quantitative and qualitative approaches, presenting exploratory and descriptive biases. Romance of Leadership Scale (RLS), by James R. Meindl (1998), according to Schyns, Meindl e Croon (2007) publication, has been applied, as well as semi-structured interviews with content analysis according to Bardin (2016). It has been observed that servants have a romanticized perspective of leadership, classified as classic romancers: those who tend to perceive the figure of the leader in a heroic and irreplaceable way. This result was reflected in interviews with servants linked to Lidere – interviews showed preponderance to the role of the leader to the detriment of other elements that should be valued for the construction of the leadership process, according to more contemporary perspectives. In addition to these results, this research generated the Portuguese translation of RLS. Regarding the factorial structure of the Portuguese version, the exploratory analysis indicated the presence of six factors.